Written on the wind [videorecording (DVD)] - Sirk, Douglas, 1897-1987; Hudson, Rock, 1925-1985; Bacall, Lauren, 1924-2014; Stack, Robert, 1919-2003; Malone, Dorothy; Wilder, Robert, 1901-1974 (Criterion collection, 2001)
"Bathed in lurid Technicolor, melodrama maestro Douglas Sirk's Written on the Wind is the stylishly debauched tale of a Texas oil magnate brought down by the excesses of his spoiled offspring. Features an all-star quartet that includes Robert Stack as a pistol-packin' alcoholic playboy; Lauren Bacall as his long-suffering wife; Rock Hudson as his earthy best friend; and Dorothy Malone as his nymphomaniac sister."--Container.